É possível aliar a psicanálise ao aconselhamento religioso? - Santos, Francisco de Assis Souza dos (2010)
Psychoanalysis was able to call the attention not only of the sciences related to human behavior (anthropology, philosophy, psychology, sociology and education, among others), but also of theology, specifically one that is directly related to psychology and pastoral counseling. Theology, religion and counselor still maintain some restrictions when it comes to pastoral counseling and psychoanalytic method of therapy to be used as a valid tool in the pastor's study sessions. Religion and its effects on human behavior are some of the most important study in Freudian psychoanalytic method. Just as theology stands before the other sciences, seeking interdisciplinary, it is healthy to maintain a means of communication that can dialogue with psychoanalysis. Thus, we seek to study what is positive in psychoanalysis and which is not at odds with the theology, especially in pastoral counseling, which can be understood as a dynamic practice closer to the model presented by Freud as therapy. In this study we intent to show that possible antagonism between the theories presented by the father of psychoanalysis and pastoral counseling, can be seen but without prejudice. We draw out what can be useful for the Christian counselor in the exercise of its function. The boundaries between pastoral counseling and psychoanalysis should not discredit the importance of this to the knowledge of the psyche and the human soul.